HUBUNGAN STATUS GIZI DAN PENGETAHUAN GIZI SEIMBANG DENGAN KEBUGARAN JASMANI PADA ATLET PENCAK SILAT PAGAR NUSA GRESIK - Hasanatun Hasanatun (Ghidza Media Jurnal, 2019)
This study aims to determine the relationship between nutritional status and balanced nutrition with physical fitness in the martial arts athlete in Pagar Nusa Gresik. This research uses a cross sectional approach. The population used is 10-18 years old who are members of the Nusa Gresik Fence. 50 athletes. Data was collected through measurements of body weight, height, and body fat percent, questionnaires, and physical fitness tests. The results showed 82% of athletes had normal BMI, 56% of athletes had healthy body fat percent, 76% of athletes had good levels of knowledge, and 685% of athletes had sufficient physical fitness levels. Statistical tests show that there is a relationship between BMI / U with physical fitness (p = 0.000), and no relationship between body fat percent (p = 0.093), balanced nutritional knowledge (p = 0.326) with physical fitness.